pH-triggered dynamic erosive small molecule chlorambucil nano-prodrugs mediate robust oral chemotherapy - Xin Liu; Zhexiang Wang; Xiaodie Ren; Xinyang Chen; Jinjin Tao; Yuanhui Guan; Xuefeng Yang; Rupei Tang; Guoqing Yan (Elsevier, 2023)
Currently, the dynamic erosive small molecule nano-prodrug is of great demand for oral chemotherapy, owing to its precise structure, high drug loading and improved oral bioavailability via overcoming various physiologic barriers in gastrointestinal tract, blood circulation and tumor tissues compared to other oral nanomedicines. Herein, this work highlights the successful development of pH-triggered dynamic erosive small molecule nano-prodrugs based on in vivo significant pH changes, which are synthesized via amide reaction between chlorambucil and star-shaped ortho esters. The precise nano-prodrugs exhibit extraordinarily high drug loading (68.16%), electric neutrality, strong hydrophobicity, and dynamic large-to-small size transition from gastrointestinal pH to tumoral pH. These favorable physicochemical properties can effectively facilitate gastrointestinal absorption, blood circulation stability, tumor accumulation, cellular uptake, and cytotoxicity, therefore achieving high oral relative bioavailability (358.72%) and significant tumor growth inhibition while decreasing side effects. Thus, this work may open a new avenue for robust oral chemotherapy attractive for clinical translation.